Virtual experiments - Sunley(3, (Bchriss; Adams(3, (Bneils; Bourne(3, (BJanes (London Harper collins, 2003)
ateaching tool designed for years 3 and 4 to demonstrate experiments as well as revise key work pupils may have missed or forgotten. you can repeat slow down and change the conditions of experiments without the usual mess and fuss they entail
age 3-11
pentium processor(3, (Bwindows 98/me/nt/2000(3, (B64 mb ram (3,(Bhigh colour(3, (B75 mb hard disc spaces
1 2
Keywords: science -- directions -- MPL; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs